ADR-MÓDSZEREK ÉS TECHNIKÁK NEMZETKÖZI KONFLIKTUSRENDEZÉSEKBEN - Illyés, Szabolcs (Kultúratudományi Szemle, 2025)
ADR Methods and Techniques in International Conflict Resolution ADR techniques significantly facilitate the development of enduring, mutually acceptable solutions in the sequence of mediation methods. In recent decades of international conflict management practices, the following four techniques have frequently been applied: arbitration, conciliation, mini-trial, and early neutral evaluation. Beyond the success of these methods, novel conflict management concepts are implemented in relation to John Paul Lederach's paradigm, William Jury's winwin strategy, and Robert Mnookin's negotiation or fight method.